ANALISIS METODE UTAUT2 UNTUK MENJELASKAN PERILAKU KONSUMEN DALAM MENGGUNAKAN E-COMMERCE DI KALANGAN MAHASISWA AKUNTANSI UNIVERSITAS DIPONEGORO - Arista Kusumaningrum; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
Theory of Planned Behavior (TPB), a consumer psychology technique proposed by Ajzen, is the consumer theory utilized in this study. A theory known as the Theory of Planned Behavior is predicated on the idea that an individual will act appropriately. In the Theory of Planned Behavior, attitudes toward behavior, subjective norms, and encountered behavioral controls are the three factors that influence behavioral intentions.In addition to TPB, the purpose of this study—also known as a case study—is to investigate how accounting students at Diponegoro University's consumer behavior when using e-commerce is explained by the factors in the UTAUT2 theory. In order to determine what factors influence behavioral intention and use behavioral in e-commerce technology, this study examines several variables in the UTAUT2 theory, including performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, and habit.The population of this quantitative study is Diponegoro University students using the Shopee application at the Faculty of Economics and Business. The entire questionnaire was completed by 109 people who used the Google form that was posted online and shared on social media. In this study, Partial Least Squares was used to analyze the data.This study's findings that students' behavioral intentions to use e-commerce are influenced by business expectations, performance expectations, and habits In addition, use behavioral are influenced by facilitating condition, habit, and behavioral intention. It has been demonstrated that other factors, such as hedonic motivation, facilitating condition, and social influence, have no effect on behavioral intentions to use e-commerce